Cortical Anaplastic Ependymoma with Significant Desmoplasia: A Case Report and Literature Review. (16th December 2013) - Elsharkawy, Alaa Eldin; Abuamona, Raid; Bergmann, Markus; Salem, Shadi; Gafumbegete, Evariste; Röttger, Ernst
Abstract : Ectopic brain anaplastic ependymomas with no connection to the ventricles are rare. We present a rare case of a 25-year-old male who presented with generalized convulsions. Computed tomography (CT), Magnetic Resonance Imaging (MRI), and magnetic resonance spectroscopy (MRS) showed characters of an intra- and extra-axial lesion. Intraoperatively, the lesion was a cortical solid mass that had no connections to the dura or to the ventricle. The histological diagnosis showed an anaplastic ependymoma with WHO grade III with distinctive desmoplasia. A literature review of ectopic anaplastic ependymomas regarding their clinical presentations, management, and prognostic factors was performed. There is a need to establish a clinically based histopathological grading system for anaplastic ependymomas. Ectopic anaplastic ependymomas should be included in the preoperative differential diagnosis.